(untitled) (CIPEEX, 2025)
Renal bioengineering emerges as a promising alternative for the development of functional kidneys intended for transplantation in patients with end-stage chronic kidney disease. This experimental study aims to evaluate the effectiveness of 430 nm LED light in the sterilization process of rat kidney scaffolds contaminated with Escherichia coli. Bacterial strains were reactivated in the laboratory, followed by determination of the minimum inhibitory concentration. Kidneys from Wistar rats were decellularized using two different protocols involving SDS or Triton X-100 with DNase, after controlled perfusion and freezing. Cortical slices of the kidneys were intentionally contaminated with E. coli and exposed to 430 nm LED light under three experimental conditions, varying the distance and intensity of exposure. After exposure, the scaffolds were incubated for one week in appropriate culture medium, followed by microbiological analysis using different agar media to quantify colony-forming units (CFUs). The 430 nm LED is expected to significantly reduce bacterial load without compromising tissue structure, proving to be a viable alternative to conventional sterilization methods, which often damage the extracellular matrix. Thus, the use of LED light may represent an important advancement in the preparation of sterile kidney scaffolds for future clinical applications in organ bioengineering.